Medial Tibial Bone Defect with Severe Varus Deformity in Osteoarthritis Kellgren Lawrence grade IV Using Primary Total Knee Arthroplasty Combined with screwing and Autologous Bone Graft: A Case Report and Technical Notes - Luthfi Lazuardi; Dicky Mulyadi; Albert Riantho (International Medical Journal Corp. Ltd, 2026)
Medial tibial bone defects in varus knee osteoarthritis pose challenges during total knee arthroplasty (TKA) due to bone loss and soft-tissue imbalance, which complicate restoration of alignment and stability. While constrained implants are an option, primary TKA with screw fixation and autologous bone grafting offers a bone-preserving, cost-effective alternative in patients with intact collateral ligaments. A 64-year-old male presented with progressive right knee pain, deformity, and inability to bear weight for nine years despite conservative treatment. Radiographs revealed tricompartmental osteoarthritis, varus deformity exceeding 15°, and a contained medial tibial defect measuring 10–12 mm. The patient underwent primary TKA via a medial parapatellar approach using a stabilized implant. The defect was reconstructed with an autologous cancellous graft harvested from the distal femoral cut and secured with two cortical screws. Cemented femoral, tibial, and polyethylene components were implanted after achieving soft-tissue balance. Postoperatively, he remained non–weight-bearing for three months, then progressed to full weight bearing. Early follow-up showed a 0°–110° range of motion, stable fixation, and early graft incorporation on radiographs. Autologous bone graft reconstruction provides a biological, economical method to restore the joint line and mechanical axis in primary TKA. Studies by Kharbanda, Sugita, and Dewidar have reported durable outcomes with stable graft incorporation. Careful preoperative planning, rigid fixation, and structured rehabilitation are essential for success. This technique offers a reliable, bone-preserving solution that achieves alignment correction and functional recovery without the need for constrained implants.